Protective effects of m-nisoldipine and nisoldipine on myocardial damage in working rabbit hearts after ischemia-reperfusion - Zhang Hai-lin; Fu Shao-xuan; Li Yun-shan (Acta Pharmacologica Sinica, 2016)
m-Nisoldipine 4, 8, 16 nmol/L, nisoldipine 1, 4 nmol/L and nifedipine 4, 8, 16, 50 nmol/L enhanced the recoveries of functional parameters of working rabbit hearts after ischemia-reperfusion, as well as prevented the development of contracture and the release of CPK from the reperfused hearts. m-Nisoldipine 8 nmol/L, nisoldipine 1 nmol/L and nifedipine 8 nmol/L attenuated the reduction of myocardial Na+-K+-ATPase and 5'-nucleotidase activity induced by ischemia-reperfusion. The breakdown of membrane phospholipids and elevation of the myocardial Ca2+-ATPase activity and the free fatty acids level were also prevented.